2019
DOI: 10.31539/leea.v2i2.349
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of English Lexical Collocation Found in English Newspaper

Abstract: This study was conducted to find out the answer of question about what the English lexical collocation found in English Newspaper, The Jakarta Post. This study was designed as a descriptive qualitative research and data of the study was described in form of qualitative description. The data was taken from the headlines of the Jakarta post newspaper which published on April 4 th -9 th 2016. The sources of the data in this study were sentences and utterances that contain collocation. Human instrument was the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this qualitative research, it was found that there were 53 words, 15 phrases, and five abbreviations containing political jargon in the political news of the CNN website, and from the 73 data, it was found that there were 58 data containing denotative meanings and 15 containing connotative meanings and also found that the function of the political jargon is to express involvement in a particular group, communicate, and indicate the identification of a particular group. Research by Yulfi, Seli, and Ariska (2019), which describes the types and meanings of English lexical collocations in an English-language newspaper, also shows problems regarding the meaning of language in mass media. This research is qualitative in nature and is conducted on sentences and utterances that have collocations (combinations of words that usually appear together) in the headlines of The Jakarta Post newspaper.…”
Section: Discussionmentioning
confidence: 99%
“…In this qualitative research, it was found that there were 53 words, 15 phrases, and five abbreviations containing political jargon in the political news of the CNN website, and from the 73 data, it was found that there were 58 data containing denotative meanings and 15 containing connotative meanings and also found that the function of the political jargon is to express involvement in a particular group, communicate, and indicate the identification of a particular group. Research by Yulfi, Seli, and Ariska (2019), which describes the types and meanings of English lexical collocations in an English-language newspaper, also shows problems regarding the meaning of language in mass media. This research is qualitative in nature and is conducted on sentences and utterances that have collocations (combinations of words that usually appear together) in the headlines of The Jakarta Post newspaper.…”
Section: Discussionmentioning
confidence: 99%
“…It was applied qualitative and quantitative method. Fifth, Yulfi et al (2019) analysed lexical collocation by using descriptive qualitative method. Sixth, Indhiarti and Chaerunnisa (2021) was examined the collocational pattern and semantic prosody.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It doesn't confine the connection of synonymy to lexemes and makes character, not just likeness, of significance to the standard of synonymy (Mirzapour & Ahmadi, 2011). Yulfi et al (2019) characterise at least two articulations are equivalent if and provided that they fulfil these three circumstances, such as (a) all their meanings are identical; (b) they are synonymous in all contexts; (c) they are semantically equivalent (their meaning or meanings are identical) on all dimensions of meaning, descriptive and non-descriptive.…”
Section: Introductionmentioning
confidence: 99%